(untitled) (Bangladesh Journal of Child Health, 2018)
Background: Precocious puberty is a common paediatric endocrine disorder seen in clinical practice. This study was carried out to find out the aetiology of precocious puberty in children presenting in a tertiary care hospital. Methodology: This cross sectional study was done at paediatric endocrine outpatient department at BIRDEM General Hospital from July 2005 to June 2015. The clinical data as well as laboratory findings were collected from consecutive patients who presented for evaluation of precocious puberty. Result: Seventy one patients presented with precocious puberty during this study period. There was female preponderance (71.8%). The mean age at presentation of girls and boys were 4.8±2.1 years and 6.63±1.4 years respectively. Among the 51 girls who presented with precocious puberty 22(43.1%) had central precocious puberty (CPP), 5(9.8%) had peripheral precocious puberty (PPP) and 24(47%) had incomplete precocious puberty (IPP). Among the 22 girls with CPP 19(86.3%) were idiopathic & 3(13.6%) girls were hypothyroid. Among the 5 girls with PPP, 3(60%) had congenital adrenal hyperplasia (CAH) & 2(40%) had adrenal adenoma. In case of incomplete precious puberty among 24 girls, 20 (83.3%) had premature thelarche, 1(4.1%) had premature menarche & 3 (12.5%) had premature adrenarche. In 20 boys with precocious puberty, 7(35%) had CPP. Among them 3(42.8%) boys had hypothalamic hamartoma, 1(14.2%) boy had craniopharyngioma and other 3(42.8%) boys had idiopathic CPP. PPP was present in 11(55%) boys. Among them 8(72.7%) patient had CAH, 2(18.1%) had adrenal adenoma and 1(9.0%) had hepatoblastoma. Premature adrenarche was present in 2(10%) boys. Conclusions: Precocious puberty was more commonly found among girls as compared to boys. Central precocious puberty was more common among girls and majority were idiopathic. Among boy precocious pseudopuberty was more common and CAH was the commonest cause. Majority of boy with central precocious puberty had organic brain lesion. Bangladesh J Child Health 2017; VOL 41 (3) :143-146